Measurement of W-boson helicity fractions in top-quark decays using cos theta - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
Fully reconstructed t over(t, ̄) → W+ b W- over(b, ̄) → ℓ ν q over(q, ̄)′ b over(b, ̄) events are used to determine the fractions of right-handed (f+) and longitudinally polarized (f0) W bosons produced in top-quark decays. The helicity fractions are sensitive to the couplings and the Dirac structure of the Wtb vertex. This Letter reports measurements of the W-boson helicity fractions from two different methods using data corresponding to an integrated luminosity of 1.9 fb- 1 of p over(p, ̄) collisions at a center-of-mass energy of 1.96 TeV collected by the CDF II detector operating at the Fermilab Tevatron. Combining the results from the two methods, we find f0 = 0.62 ± 0.10 (stat) ± 0.05 (syst) under the assumption that f+ = 0, and f+ = - 0.04 ± 0.04 (stat) ± 0.03 (syst) with f0 fixed to the theoretically expected value of 0.70. Model-independent fits are also performed and simultaneously determine f0 = 0.66 ± 0.16 (stat) ± 0.05 (syst) and f+ = - 0.03 ± 0.06 (stat) ± 0.03 (syst). All these results are consistent with standard model expectations. © 2009 Elsevier B.V.